Studi Literatur: Peran Guru Penggerak Dalam Rangka Peningkatan Kualitas Pendidikan Nasional - Palobo, Agri Felisitas; Yoenanto, Nono H (Pedagogi: Jurnal Ilmu Pendidikan, 2024)
This research aims to describe the role of driving teachers in efforts to improve the quality of national education. The method used is a literature review study method from 12 sources consisting of 3 books and 9 journals from Google Play Books, Google Scholar, and Research Gate using the keywords "quality of education" and "motivating teachers". The results of the literature study show that Indonesian education is still haunted by several problems that affect the quality of national education. This problem is divided into two scopes, namely macro and micro scope. The causes of the low quality of education in Indonesia include three factors, such as an education system that is not running optimally, a curriculum that is always changing and teacher competence. The role of driving teachers can encourage some improvements in the quality of national education where teachers act as learning agents who make the learning process student-centered.